TWO INDIAS: FEDERALISM, REGIONALIZATION, AND THE 2024 GENERAL ELECTIONS - Djogatovic, Veljko (Serbian political thought, 2025)
This paper explores the profound social, cultural, and political divisions between Northern and Southern India, with a particular focus on their impact on the outcomes of the 2024 general elections. Starting from the hypothesis that the North-South divide in India – rooted in linguistic, religious, economic, and cultural differences – directly shapes political dynamics, the paper analyses how these differences have become institutionalized through the party system and regional political organization. The North, dominated by the Hindu-nationalist Bharatiya Janata Party, stands in contrast to the South, where regional parties and a more liberal political discourse are gaining strength. This contrast contributes to the deepening of a dual-party or dual-coalition system and further intensifies political polarization. The paper also considers the historical context, including the legacy of colonialism, religious and cultural identities, and economic disparities that fuel regional tensions. The research finds that India’s federal framework is increasingly challenged by rising political and cultural-identity polarization, which ultimately carries far-reaching consequences for the stability and integration of the state.